Art and human nature xxi - Musso, Carlos G.; Enz, Paula A. (Revista del Hospital Italiano de Buenos Aires, 2015)
Through his painting technique, Giuseppe Arcimboldo shows how solidarity is a universal principle that achieves the harmony of the multiplicity and diversity of the simple, from which may arise the complexity of the great